2015
DOI: 10.1111/1462-2920.12801
|View full text |Cite
|
Sign up to set email alerts
|

The hidden seasonality of the rare biosphere in coastal marine bacterioplankton

Abstract: Rare microbial taxa are increasingly recognized to play key ecological roles, but knowledge of their spatio-temporal dynamics is lacking. In a time-series study in coastal waters, we detected 83 bacterial lineages with significant seasonality, including environmentally relevant taxa where little ecological information was available. For example, Verrucomicrobia had recurrent maxima in summer, while the Flavobacteria NS4, NS5 and NS2b clades had contrasting seasonal niches. Among the seasonal taxa, only 4 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
106
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 68 publications
17
106
1
Order By: Relevance
“…Nitrogen limitation in the Bay of Banyuls-sur-mer appears during summer whereas N:P ratio increases in winter-early spring [32]. We should also mention that changes in bacterial abundance, growth as well as community composition discussed below may be related to the confinement (e.g., [33,34]). However, we tried to overcome this limitation by using the largest possible volume incubation vessels (20 L)—vessel size was limited by e.g., water volume to be sterilized—since it has been shown that bottle-effect increases for volumes <1 L [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen limitation in the Bay of Banyuls-sur-mer appears during summer whereas N:P ratio increases in winter-early spring [32]. We should also mention that changes in bacterial abundance, growth as well as community composition discussed below may be related to the confinement (e.g., [33,34]). However, we tried to overcome this limitation by using the largest possible volume incubation vessels (20 L)—vessel size was limited by e.g., water volume to be sterilized—since it has been shown that bottle-effect increases for volumes <1 L [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, all samples from day 0, and in particular Banyuls and Woods Hole, showed high similarity. Samples from the exponential growth (d5) and the stationary phase (d17) were mostly grouped together and separately from the day 0 samples, as expected after the selection that takes place in the beginning of the growth phase in batch cultures, also probably related to the confinement [33]. Moreover, differences in the dynamics of ubiquitous phylotypes (e.g., OTU1) and the selection for different phylotypes in each treatment (e.g., OTU1 in Banyuls, OTU6 in Pagasitikos, OTU9 in Woods Hole) (Table S1) were evidenced during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the two main bacterial groups detected in environmental samples based on their nucleic acid content (HNA and LNA), appear to be taxonomically different (Zubkov et al 2001;Mary et al 2006;Vila-Costa et al 2012) with little overlap between them (Schattenhofer et al 2011). In particular, the widespread SAR11 clade has been associated with LNA cells in different studies (Mary et al 2006;Schattenhofer et al 2011;Morán et al 2015). Here, we found a drastic decrease in Accepted Article cytometric diversity in a sample collected in May 2012, when almost no LNA cells were recorded in the samples ( Figure 5A) and SAR11 populations were strongly depleted (Alonso-Sáez et al 2015;Morán et al 2015).…”
Section: Estimated Cytometricmentioning
confidence: 99%
“…In particular, the widespread SAR11 clade has been associated with LNA cells in different studies (Mary et al 2006;Schattenhofer et al 2011;Morán et al 2015). Here, we found a drastic decrease in Accepted Article cytometric diversity in a sample collected in May 2012, when almost no LNA cells were recorded in the samples ( Figure 5A) and SAR11 populations were strongly depleted (Alonso-Sáez et al 2015;Morán et al 2015). This data point with the lowest cytometric diversity increased the correlation found with the Shannon-Weaver index between both methods (Figure 2) and also in the Mantel test results (Figure S3), although the relationship between both approaches remained significant after removing this value (Mantel test, r = 0.44, p = 0.001).…”
Section: Estimated Cytometricmentioning
confidence: 99%
“…Most of the recent research addressing the issue of activity within aquatic microbial communities, and particularly within the rare biosphere, has focused on the analysis of ratios of 16S rRNA to rRNA genes (rDNA) of individual bacterial taxa, the application of probe-based cell analysis or stable-isotope probing within a limited amount of samples or in the exploration of temporal patterns of specific microbial populations (e.g., Campbell et al, 2011; Hugoni et al, 2013; Vergin et al, 2013; Alonso-Sáez, 2014; Aanderud et al, 2015; Alonso-Sáez et al, 2015). These studies have provided fundamental insight into the distribution of activity and population dynamics within specific bacterial communities, but they do not provide a broad perspective on how taxa reactive and non-reactive to environmental conditions are distributed across aquatic ecosystems, particularly within the rare biosphere.…”
Section: Introductionmentioning
confidence: 99%